(untitled) (Signifiances (Signifying), 2023)
Multiple researches have used non-words to examine whether there is a motivated link between the signifier and its signified, referent or concept. Since non-words are not natural linguistic units, their treatment might be different from those belonging to natural language such as human proper names. In this paper, we focus on studies of associations between real proper names’ phonetic features and persons’ or fictional characters’ properties. We establish several tables of the phonosemantic correlations attested in previous research and we argue that it is important to explicitly present the methodology in future descriptive and experimental research.